Feline Morbillivirus Infection Associated With Tubulointerstitial Nephritis in Black Leopards (Panthera pardus). Issue 6 (November 2020) - Piewbang, Chutchai; Chaiyasak, Surangkanang; Kongmakee, Piyaporn; Sanannu, Saowaphang; Khotapat, Pornsuda; Ratthanophart, Jadsada; Banlunara, Wijit; Techangamsuwan, Somporn
Feline morbillivirus (FeMV) is an emerging RNA virus in the Paramyxoviridae family that was recently discovered in domestic cats ( Felis catus ). To date, 2 genotypes (FeMV-1 and FeMV-2) have been detected in cats from various countries, and FeMV-1 is recognized as a pathogen associated with nephritis. However, information regarding the pathological roles and potential transmission to other felids is limited. In this article, we describe the identification of FeMV in 2 black leopards ( Panthera pardus ) in Thailand that showed severe azotemia and tubulointerstitial nephritis. Molecular analysis of the partial coding sequence of the L gene revealed that these leopard FeMV strains were genetically close to the FeMV-1 isolate from domestic Thai cats. Immunohistochemistry and immunofluorescence analyses using polyclonal IgG antibodies against the FeMV matrix (M) protein showed FeMV-M antigen in renal tubular epithelial cells. These analyses also showed infiltrating lymphocytes in the renal parenchymal lesions and in the cytoplasm of lymphoid cells residing in the spleen, suggesting viral tropism and a possible pathological role. These findings are the first evidence that indicates that the black leopard could be a possible host for FeMV infection. As for other cats, the role of FeMV as a potential cause of renal disease remains to be established. The pathogenesis of FeMV infection in black leopards, or in other wild felids, through a viral transmission mechanism warrants further investigation.